Origin and evolution of gold-bearing fluids in a carbon-rich sedimentary basin: a case study of the Algamarca epithermal gold-silver-copper deposit, northern Peru - (:unkn) unknown (Elsevier BV, 2024)
Sediment-hosted gold deposits account for the major part of economic gold in the Earth's crust. However, the origin of the gold-bearing fluid and its evolution in sedimentary basins in the presence of organic carbon and its metamorphosed products such as...
Keywords: Fluidos mineralizantes; Depósitos epitermales